EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW II DAN THINK PAIR SHARE DITINJAU DARI KECERDASAN EMOSIONAL SISWA SMP SE-KOTA KEDIRI TAHUN PELAJARAN 2012/2013 - Andriani, Desi Gita; Kusmayadi, Tri Atmojo; Mardiyana, Mardiyana (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aim of the research was to determine the effect of learning models (Jigsaw II, TPS and direct learning) on mathematics achievement viewed from student emotional quotient. The type of the research was quasi experimental research using design factorial 3x3. The population was the students in grade VII junior high school in a city of Kediri. The size of the sample was 339 students. Before giving the treatment, the population had to in balance condition. The balance test used unbalance one way analysis of variance. Test requirements included normality test used Lilliefors method and the homogeneity test used Bartlett method. The hypothesis test used unbalance two ways analysis of variance. The conclusions of the research were as follows. (1) Students who taught by cooperative learning model of Jigsaw II type give better mathematics learning achievement than TPS type and direct learning and the students who taught by cooperative learning model of TPS type give better mathematics learning achievement than direct learning. (2) Students who have high emotional quotient have better mathematics learning achievement than students who have middle and low emotional quotient and then students who have middle emotional quotient have better mathematics learning achievement than students who have low emotional quotient. (3) For students who thougt by cooperative learning model of Jigsaw II type, TPS type, and direct learning, students who have high emotional quotientÂ haveÂ better mathematics learning achievement than students who have middle and low emotional quotient and then students who have middle emotional quotient have better mathematics learning achievement than students who have low emotional quotient. (4) For students who have high, middle, and low emotional quotient, students who thougt by cooperative learning model of Jigsaw II type give better mathematics learning achievement than TPS type and direct learning and the students who taught by cooperative learning model of TPS type give better mathematics learning achievement than direct learning. Keywords : Jigsaw II, TPS, and emotional quotient. Â